Recovery from Unrecognized Sleep Loss Accumulated in Daily Life Improved Mood Regulation via Prefrontal Suppression of Amygdala Activity - Motomura, Yuki; Kitamura, Shingo; Nakazaki, Kyoko; Oba, Kentaro; Katsunuma, Ruri; Terasawa, Yuri; Hida, Akiko; Moriguchi, Yoshiya; Mishima, Kazuo (Frontiers in Neurology, 2017)
Many modern people suffer from sleep debt that has accumulated in everyday life but is not subjectively noticed (potential sleep debt [PSD]). Our hypothesis for this study was that resolution of PSD through sleep extension optimizes mood regulation by altering the functional connectivity between the amygdala and prefrontal cortex. Fifteen healthy male participants underwent an experiment consisting of a baseline evaluation followed by two successive interventions, namely, a 9-day sleep extension followed by one night of total sleep deprivation (TSD). Tests performed before and after the interventions included a questionnaire on negative mood and neuroimaging with arterial spin labeling MRI for evaluating regional cerebral blood flow (rCBF) and functional connectivity. Negative mood and amygdala rCBF were significantly reduced after sleep extension compared with baseline. The amygdala had a significant negative functional connectivity with the medial prefrontal cortex (FCamg-MPFC), and this negative connectivity was greater after sleep extension than at baseline. After TSD, these indices reverted to the same level as at baseline. An additional path analysis with structural equation modeling showed that the FCamg-MPFC significantly explained the amygdala rCBF and that the amygdala rCBF significantly explained the negative mood. These findings suggest that the use of our sleep extension protocol normalized amygdala activity via negative amygdala–MPFC functional connectivity. The resolution of unnoticed PSD may improve mood by enhancing frontal suppression of hyperactivity in the amygdala caused by PSD accumulating in everyday life.